The Effect of Earthquake Disaster Educational Videos on Student Preparedness - Setyaningrum, Niken; Darmawan, Ardhian Indra (GLOBAL HEALTH SCIENCE GROUP, 2023)
Earthquakes are a disaster that continues to occur to this day, events that cannot be predicted accurately can cause damage and casualties. The island of Java, specifically the Special Region of Yogyakarta, has a history of earthquakes which have resulted in many fatalities and damage to buildings. The majority of victims are children and the elderly because they fall into a vulnerable group. The factor causing the emergence of many victims is due to a lack of knowledge about disaster preparedness. Not all children get the knowledge how to deal with the disaster if it does happen. Objective: The purpose of this study was to determine the level of preparedness for students before and after receiving education about earthquake disasters through video media Method: This type of research uses pre-experimental with pre and posttest one group. The research sample size was 37 respondents using total sampling. The instruments used are standard and have been tested for reliability and validity. Data analysis used the Wilcoxon Sign Rank Test. Results: the study show the effect of earthquake disaster educational videos on student preparedness with a p-value of 0.000. Conclusions : this study is that earthquake disaster educational videos can increase student preparedness in dealing with disasters